2006
DOI: 10.1007/s11064-005-9031-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2-deoxy-d-Glucose on Aminoacids Metabolism in Rats’ Cerebral Cortex Slices

Abstract: We studied the effect of different concentrations of 2-deoxy-D-glucose on the L-[U-14C]leucine, L-[1-14C]leucine and [1-14C]glycine metabolism in slices of cerebral cortex of 10-day-old rats. 2-deoxy-D-glucose since 0.5 mM concentration has inhibited significantly the protein synthesis from L-[U-14C]leucine and from [1-14C]glycine in relation to the medium containing only Krebs Ringer bicarbonate. Potassium 8.0 mM in incubation medium did not stimulate the protein synthesis compared to the medium containing 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The flask contents were homogenized and transferred to tubes. 28 Lipid and protein synthesis After centrifugation, the precipitate was washed 3 times with (1 mL) 10% TCA, and lipids were extracted with chloroform/methanol (2:1). The chloroform/methanol phase was evaporated in vials and radioactivity was measured.…”
Section: Co 2 Productionmentioning
confidence: 99%
“…The flask contents were homogenized and transferred to tubes. 28 Lipid and protein synthesis After centrifugation, the precipitate was washed 3 times with (1 mL) 10% TCA, and lipids were extracted with chloroform/methanol (2:1). The chloroform/methanol phase was evaporated in vials and radioactivity was measured.…”
Section: Co 2 Productionmentioning
confidence: 99%
“…For example, reduced glycolytic flux might lead to compensatory mitochondrial biogenesis and an increase in energy reserve (10) initiated in astrocytes, which are the predominant locus of glycolysis in the brain. Also, potentially relevant to 2‐DG antiepileptogenic actions, Muller et al recently reported that 2‐DG inhibits protein synthesis in immature rodent brain (11). Finally, 2‐DG may have a different profile of activity in conventional seizure models than does the KD (12), suggesting that it is unlikely to truly replace the KD.…”
Section: Commentarymentioning
confidence: 99%